(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The paper is an examination and exploration of the representation of women and their sexual desires in Manju Kapur’s “A Married Woman” and Ismat Chugtai’s “Lihaaf.” Both these works strongly condemn the shackles of the patriarchal world by presenting the New Woman, who revolts against the set norms and is very clear about her rights and desires. Lesbianism, highlighted in both these works, is an attack on conventional society and shows how it is a matter of self-identity for a woman. This paper is an attempt to understand the psyche and position of sexually repressed women and will explore their struggles in their quest for identity and assertion of individuality. Through this paper, I intend to focus on the situation of sexually repressed women, the trauma she has to go through, and her protests for self-recognition.